History of the Second World War - General Advisory Editor O'Neill H. C. (London Odhams Press Limited, 1951)
One-volume military history of World War II, written by a British historian.
Include Illustration
Keywords: Military Campaigns -- Guerre Mondiale, 1939-1945 -- World War (1939-1945)